1997
DOI: 10.1097/00005792-199707000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcal Bacteremia: A 10-Year Prospective Study

Abstract: In this paper we present a prospective evaluation of 100 patients with Group A Streptococcal (GAS) bacteremia evaluated in our hospital over a 10-year period. Sixty-two patients were intravenous drug users (IVDU); all but 1 of these had an obvious cutaneous portal of entry related to the injection of illicit drugs. Twenty-seven patients had infectious metastasis, and the presence of septic pulmonary embolism was associated with suppurative phlebitis. Four of these patients had endocarditis. In the non-IVDU gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Broyles et al [4] reported that 6% (12 out of 212) of patients with invasive S. dysgalactiae infection in the Atlanta metropolitan area (Georgia, USA) and San Francisco Bay metropolitan area (California, USA) were IVDUs. In the 1990s, associations of IV-DU and beta-haemolytic streptococcal bacteraemia were reported with group A Streptococcus (GAS) [12,13]. Similarly, epidemics and endemic disease caused by GAS was reported in IVDUs in our geographic area (Bern, Switzerland) in 2001 [14].…”
Section: Discussionmentioning
confidence: 92%
“…Broyles et al [4] reported that 6% (12 out of 212) of patients with invasive S. dysgalactiae infection in the Atlanta metropolitan area (Georgia, USA) and San Francisco Bay metropolitan area (California, USA) were IVDUs. In the 1990s, associations of IV-DU and beta-haemolytic streptococcal bacteraemia were reported with group A Streptococcus (GAS) [12,13]. Similarly, epidemics and endemic disease caused by GAS was reported in IVDUs in our geographic area (Bern, Switzerland) in 2001 [14].…”
Section: Discussionmentioning
confidence: 92%
“… Species Patient ( n ) age/sex Risk factors Therapy Decease References Cases of bacteremia and general infections Streptococcus viridans 45/M Teeth and gums disease Ill teeth extraction N [ 81 ] Streptococcus salivarius n = 30 Endocarditis 3 [ 82 ] 22/M Group C Streptococcus n = 88 Basic disease 72.7 % β-lactams 25 % [ 83 ] Streptococcus pneumoniae n = 590 19 % [ 84 ] Streptococcus spp. n = 100 Intravenous drug abuse, infectious metastases, purulent vein inflammation, endocarditis 6 [ 85 ] 20–40/F Streptococcus pneumoniae n = 55 Amoxicillin, clarithromycin, azithromycin, ceftriaxone, ceftibuten, cefaclor [ 86 ] 0–5 years Streptococcus pneumoniae n = 71 HIV Third-generation cephalosporins, vancomycin, or erythromycin 28 % [ 87 ] 42/M Streptococcus spp. n = 522 [ 88 ] Viridans group Streptococcus n = 79 (88 episodes) Leukemia/stem cell transplantation Piperacillin and gentamicin, piperacillin and tobramycin, or ceftazidime and tobramycin [ …”
Section: Sepsismentioning
confidence: 99%